2014
DOI: 10.1111/oik.01540
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐symbiotic systems: functional implications of the coexistence of grass–endophyte and legume–rhizobia symbioses

Abstract: The coexistence of symbionts with different functional roles in co‐occurring plants is highly probable in terrestrial ecosystems. Analyses of how plants and microbes interact above‐ and belowground in multi‐symbiotic systems are key to understand community structure and ecosystem functioning. We performed an outdoor experiment in mesocosms to investigate the consequences of the interaction of a provider belowground symbiont of legumes (nitrogen‐fixing bacteria) and a protector aerial fungal symbiont of grasses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 57 publications
(79 reference statements)
3
27
0
Order By: Relevance
“…Schipanski and Drinkwater (2012) estimated that in red clover-orchardgrass mixtures, N fixation activity increased by 15 % due to transfer of fixed N between species. García Parisi et al (2014) also found that asexual Epichloë spp. infection of annual ryegrass almost doubled N fixation activity and biomass in neighboring white clover despite a reduction in nodulation.…”
Section: Discussionmentioning
confidence: 93%
“…Schipanski and Drinkwater (2012) estimated that in red clover-orchardgrass mixtures, N fixation activity increased by 15 % due to transfer of fixed N between species. García Parisi et al (2014) also found that asexual Epichloë spp. infection of annual ryegrass almost doubled N fixation activity and biomass in neighboring white clover despite a reduction in nodulation.…”
Section: Discussionmentioning
confidence: 93%
“…In a recent study, we found that Epichloë endophyte colonization significantly inhibited AMF colonization of the host grass Achnatherum sibiricum, and the effects of AMF on host competition were variable and depended on the identity of the AMF species [18]. As AMF diversity is high in natural grasslands, and Epichloë endophyte colonization can affect AMF as well as other microbes [32][33][34], we hypothesized that Epichloë endophyte colonization could not only affect the competitive ability of the host directly by changing its growth and resistance, but also indirectly by changing soil microbes.…”
Section: Introductionmentioning
confidence: 93%
“…Epichloë endophytes may not only affect the growth and resistances of host grasses, but may also affect soil microbes, such as nitrogen-fixing bacteria, phosphorus-solubilizing rhizospheric fungi, arbuscular mycorrhizal fungi (AMF) and other microbial communities [30][31][32][33]. Can Epichloë endophyte-mediated modification of soil microbes affect the competitive ability of host grasses indirectly?…”
Section: Introductionmentioning
confidence: 99%
“…Omacini et al [79] reported that rhizobia were sensitive to endophytic fungi. García Parisi et al [80] found that endophytic fungi could inhibit the number of nodules in leguminous plants but did not affect their growth. Our study found that rhizobia inoculation could significantly increase clover biomass when mixed with E− tall fescue; however, when mixed with E+ plants, the beneficial effect of rhizobia inoculation on clover disappeared.…”
Section: Rhizobia Inoculation Can Alleviate the Detrimental Effect Ofmentioning
confidence: 99%